SARS-CoV-2 Infection-and mRNA Vaccine-induced Humoral Immunity among Schoolchildren in Hawassa, Ethiopia - Merid, Yared; Tekleselasie, Wondwosen; Tesfaye, Emnet; Gadisa, Anteneh; Fentahun, Dessalegn; Abate, Alegntaw; Alemu, Aynalem; Mihret, Adane; Mulu, Andargachew; Gelanew, Tesfaye (Frontiers in Immunology, 2023)
With the persisting low vaccination intake, particularly in children of low-and middle-income countries (LMICs), seroepidemiological studies are urgently needed to guide and tailor COVID-19 pandemic response efforts in schools and to place mitigation strategies for future postpandemic resurgence. However, there is limited data on SARS-CoV-2 infection-induced and vaccine-induced humoral immunity in schoolchildren in LMICs, including Ethiopia. As the receptor binding domain (RBD) is the major target for neutralization antibodies and useful to predict the correlates of protection, we used an in-house anti-RBD IgG ELISA to assess and compare infection-induced antibody response at two-time points and BNT162b2 (BNT) vaccine-induced antibody response at a one-time point in schoolchildren in Hawassa, Ethiopia. When we compare SARS-CoV-2 infection-induced seroprevalences among unvaccinated school children (7-19 years) at the two blood sampling points with a five-month interval, we observed an over 10% increase, from 51.8% (219/419) in the first week of December 2021 (pre-Omicron wave) to 67.4% (60/89) by the end of May 2022 (post-Omicron wave) in schoolchildren (7-19 years). Additionally, we found a significant correlation (P = 0.001) between anti-RBD IgG seropositivity and a history of having COVID-19-like symptoms. Compared to the levels of SARS-CoV-2 infection-induced anti-RBD IgG antibodies before vaccination, higher levels of BNT vaccine-induced anti-RBD IgG antibodies were observed even in SARS-CoV-2 infection-naïve children of all age groups (P = 0.0001). Importantly, one dose of BNT vaccine was shown to be adequate to elicit a strong antibody response in children with pre-existing anti-RBD IgG antibodies comparable to that of SARS-CoV-2 infection naive children receiving two doses of BNT vaccine, suggesting a single dose administration of the BNT vaccine could be considered for children who had prior SARS-CoV-2 infection when a shortage of vaccine supply is a limiting factor to administer two doses irrespective of their serostatus. Albeit small size of the study participants, the BNT vaccine is immunogenic and safe for schoolchildren.